Crystallite Morphology‐Dependent Optical Temperature‐Sensing Properties of Eu3+‐Doped NaGd(WO4)2 Phosphor. Issue 35 (19th December 2017) - Ming, Xin; Meng, Qingyu; Lü, Shuchen; Sun, Wenjun
Abstract: NaGd(WO4 )2 : Eu 3+ phosphors by using sodium citrate (Na3 Cit, Na3 C6 H5 O7 ) as chelating agent were synthesized via hydrothermal method. The structure and morphology were characterized and analyzed by the X‐ray diffraction and field emission scanning electron microscopy. Adding Na3 Cit into the reaction solution can considerably influence the crystallite morphologies of the samples. The temperature dependent photoluminescence spectra of NaGd(WO4 )2 : Eu 3+ phosphors with different ratios of Cit 3− /Re 3+ have been measured. It was found that, in the NaGd(WO4 )2 : Eu 3+ phosphors, the optical temperature sensing can be achieved by following three temperature dependent parameters: the ratio of luminous intensity of thermally coupled energy levels ( 5 D0 and 5 D1 ); the emission intensities of Eu 3+ 5 D0 ‐ 7 F2 transition; the Huang‐Rhys factor of Eu 3+ 7 F0 ‐ 5 D2 transition absorption. And the temperature sensing sensitivities of all three methods increased with increase of the ratios of Cit 3− /Re 3+ . This is mainly due to that the number of crystal defects increases with increase of the concentration of Cit 3−, and the vibration modes and number of phonons increase, so the intensity of electron‐phonon coupling increases. Abstract : NaGd(WO4 )2 : Eu 3+ phosphors were prepared by hydrothermal method. The optical temperature sensing can be achieved by following three parameters: the ratio of luminous intensity of thermally coupled energy levels ( 5 D0 and 5 D1 ); the emission intensities of Eu 3+ 5 D0 ‐ 7 F2 transition; the Huang‐Rhys factor of Eu 3+ 7 F0 ‐ 5 D2 transition absorption, these three methods can be used to verify each other.